Restorative Justice in The Settlement of Fraud Crimes in The Banyumas Police Criminal Investigation Unit - Marsitiningsih Marsitiningsih; Ira Citra Ningrom; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
The settlement of fraud cases with restorative justice is an innovative step to follow the dynamics of the development of the legal world which began to shift from positivism to progressive. Restorative justice is an approach that focuses more on the conditions for the creation of justice and balance for the perpetrators of criminal acts and the victims themselves. The research method used is empirical juridical, namely legal research on the implementation of restorative justice in action in the settlement of fraud cases by the Banyumas Police Criminal Investigation Unit. The purpose of this research is to analyze the settlement of fraud crimes through restorative justice and to find out the obstacles in the settlement of theft crimes through restorative justice at Satreskrim Polresta Banyumas. The results showed that the Banyumas Police Criminal Investigation Unit resolved fraud cases using a restorative justice approach based on Police Regulation Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice, namely by bringing together the perpetrator and victim and seeking to restore the losses suffered by the victim. The obstacles faced by Satreskrim Polresta Banyumas are that the victim does not want the involvement of outside parties in resolving his case and the inability of the perpetrator to fulfill the compensation requested by the victim, causing the settlement of fraud cases through restorative justice to fail.